The Portuguese element in linguistics and onomastics universes of Guinea Gulf : study of cases - (:unkn) unknown (My University, 2010)
From XVth to XVIIth century, Portugal has been ranking first among the most advanced nations of its time. It is during that era that the explorers helped this country to reach out Africa, Asia, America and Oceania. But any contact with peoples and cultures has always been a source of various and multifaceted reciprocal influences. In this thesis, we will study the lusitanian impressions in the Guinea Gulf. The research has been conducted in the southern part of Ivory Coast, Ghana, Togo and Benin and is based on a corpus made up of some hundreds of words that we have listed in a bibliography and an investigation that we have carried out in the field during eight years. The analysis of data is done according to a bipolar method which combines history and structuralism in its contrastive approach because, in reality, we are comparing two linguistic systems: portuguese, kru and kwa languages of the Niger-Congo family. The study includes three parts; the first part deals with the historical background of luso-african relationships then delineates the targeted geographic realms; the second part studies the portuguese lexical borrowings in the main languages of the region; finally, the third and last part touches on the issue of portuguese onomastic borrowings in the region.
Keywords: African Research